ANALISIS PERILAKU MASYARAKAT DALAM MENUNAIKAN ZAKAT PERTANIAN - Firdaus, Rahmad; Sartika, Cici (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2022)
As for the results of the research, the authors found that the behavior of muzakki in paying agricultural zakat was carried out by means of self-calculation, namely by using the method of calculating agricultural zakat 71.4% and 28.6% by using calculations that did not follow sharia rules, namely in accordance with sincerity. Most of the muzakki pay zakat according to haul 92.9% and those who pay during Ramadan 7.1%. While the place to pay zakat, most of the muzakki pay directly to mustahik 92.9%, namely mosques, neighbors or families who are less fortunate and 7.1% pay through BAZNAS institutions. As well as the forms of agricultural zakat distributed by muzakki there are in two forms, namely in the form of cash and rice. 71.4% of the interviewees paid in cash and 28.6% paid zakat in the form of rice or paddy. Zakat adalah pengeluaran harta yang wajib dikeluarkan oleh orang muslim dan diberikan membantu program pemerintah dan mengentaskan kemiskinan. Maka dari itu membayar zakat dapat berguna juga untuk kemajuan suatu negara. peran zakat adalah sebagai pengendali keuangan di dalam negara yang dikenal dengan kebijakan moneter. Karena zakat termasuk dalam pendapatan negara yang disalurkan untuk mensejahterakan masyarakat di bidang ekonomi seperti, kesempatan peluang kerja, keadilan distribusi pendapatan dan kekayaan, serta stabilitas nilai uang.kepada golongan yang berhak menerimanya untuk memenuhi kebutuhan serta meningkatkan pemerataan pertumbuhan ekonomi. Membayar zakat sangat memberi manfaat untuk kehidupan karena dapat meningkatkan iman seseorang pada Allah SWT. Selain itu, zakat juga ikut.